An enhanced WPA2/PSK for preventing authentication cracking - Chin-Ling Chen; Supaporn Punya (Institute of Advanced Engineering and Science, 2021)
Wi-Fi Protected Access 2 (WPA 2) currently is the most widely used mechanism for protecting the users in wireless networks. We have discussed the weakness of 4-way handshake procedure in Wi-Fi WPA2/PSK and proposed an enhance WPA2/PSK by adding timestamp parameter to prevent authentication cracking. The experiments have compared WPA2/PSK with Enhanced WPA2/PSK cracking and the result is also given.